A recombinant vesicular stomatitis virus replicon vaccine protects chickens from highly pathogenic avian influenza virus (H7N1) - Kalhoro, Nazeer H.; Veits, Jutta; Rautenschlein, Silke; Zimmer, Gert (Vaccine, 2009)
Highly pathogenic avian influenza viruses (HPAIV) of subtypes H5 and H7 cause fatal disease in poultry (fowl plague) but also have zoonotic potential. Currently commercially available vaccines often do not provide sufficient protection and do not allow easy discrimination between vaccinated and infected birds. Therefore, vaccination of domestic poultry against H5 and H7 HPAIV is not allowed in many countries, or is only possible after special permission has been provided. We generated a recombinant marker vaccine based on non-transmissible vesicular stomatitis virus (VSV) expressing the HA antigen of HPAIV A/FPV/Rostock/34 (H7N1) in place of the VSV G gene. This virus, VSV*ΔG(HA), was propagated on a helper cell line providing VSV G in trans. Since no progeny virus was produced after infection of non-complementing cells, the vector was classified as biosafety level 1 organism (“safe”). Chickens were immunized via the intramuscular route. Following booster vaccination with the same replicons high titers of serum antibodies were induced, which neutralized avian influenza viruses of subtypes H7N1 and H7N7 but not H5N2. Vaccinated chickens were protected against a lethal dose of heterologous HPAIV A/chicken/Italy/445/99 (H7N1). Secretion of challenge virus was short-term and significantly reduced. Finally, it was possible to discriminate vaccinated chickens from infected ones by a simple ELISA assay. We propose that VSV replicons have the potential to be developed to high-quality vaccines for protection of poultry against different subtypes of avian influenza viruses.